PENGARUH PEMBERIAN BANTUAN PEMBANGUNAN RUMAH PADA MASYARAKAT MISKIN TERHADAP SIKAP BERAGAMA DI KOTA PADANGSIDIMPUAN - M.Si, REPLITA _ (Institut Agama Islam Negeri Padangsidimpuan, 2015)
The background of this title researched, is given there are still many poor people in the Padangsidimpuan city, where of BPS data on Padangsidimpuan city in 2013 showed that there is still a poverty rate of 8.5%, through the funds of PACKAGE PNPM Urban, so the government can assist to empower poor communities with various activities such as housing assistance. People who receive assistance usually seen in its behavior in worship and society worship which is the better, such as increased taklim diligently Islamic gathering of other religious and social activities. The results showed that with the provision of housing assistance by PNPM Mandiri in society, the more diligent they are to pray.